2021
DOI: 10.1007/s12032-021-01502-0
|View full text |Cite
|
Sign up to set email alerts
|

SNRPB is a mediator for cellular response to cisplatin in non-small-cell lung cancer

Abstract: Background: Our previous study has demonstrated that small nuclear ribonucleoprotein polypeptides B And B' (SNRPB) is highly expressed in non-small-cell lung cancer (NSCLC) and functions as an oncogene. However, whether SNRPB contributes to cisplatin resistance in NSCLC is still unknown. This study aimed to explore how SNRPB regulates the effect of cisplatin in NSCLC.Methods: In this study, cell counting kit-8 (CCK-8) and ow cytometry assays were performed to examine cell survival, cell cycle and apoptosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Previous study reported that SNRPB promotes the tumor formation of NSCLC by regulating RAB26 and SNRPB may predict response to cisplatin-based chemotherapy for NSCLC patients ( Liu et al, 2019 ; Liu et al, 2021 ). Here, the mRNA expression of SNRPB was found to be upregulated in LUAD compared to non-cancer tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Previous study reported that SNRPB promotes the tumor formation of NSCLC by regulating RAB26 and SNRPB may predict response to cisplatin-based chemotherapy for NSCLC patients ( Liu et al, 2019 ; Liu et al, 2021 ). Here, the mRNA expression of SNRPB was found to be upregulated in LUAD compared to non-cancer tissues.…”
Section: Discussionmentioning
confidence: 98%
“…The molecules B/D1/D2/D3/E/F/G are the core Sm proteins that make up splice snRNPs and have a significant role in the development of cancer, according to previous research [ 18 ]. SNRPB is significantly linked to cisplatin resistance in NSCLC, and overexpressed SNRPBs enhance the inhibitory effect of cisplatin on H460 cell-mediated xenografted tumors [ 19 , 20 ]. SNRPB can mediate RNA splicing and drive the proliferation and dryness of tumor cells in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The basic findings provide clues regarding the mechanisms of the adverse effects of SNRPB on tumor prognosis. SNRPB not only promotes tumor proliferation, migration, and metastasis but also maintains the stemness of tumor cells ( Zhan et al, 2020 ) and affects tumor responsiveness to therapy ( Liu et al, 2021 ). Therefore, SNRPB may be involved in many aspects, such as tumorigenesis, progression, metastasis, maintenance of stemness, and treatment responsiveness, acting with adverse effects on the prognosis of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The protein translated by these new mRNA variants may play an important role in tumorigenesis ( Correa et al, 2016 ; Liu et al, 2019 ; Peng et al, 2020 ; Zhan et al, 2020 ). The role of SNRPB in promoting tumorigenesis and progression has been observed in tumors such as non-small cell lung cancer (NSCLC) ( Liu et al, 2019 ; Liu et al, 2021 ), hepatocellular carcinoma (LIHC) ( Peng et al, 2020 ; Zhan et al, 2020 ; Li et al, 2022 ), glioblastoma (GBM) ( Correa et al, 2016 ), cervical cancer (CESC) ( Zhu et al, 2020 ), and thyroid carcinoma (THCA) ( Deng et al, 2022 ). However, the role of SNRPB in other tumors remains unclear.…”
Section: Introductionmentioning
confidence: 99%